Effect of substrate‑shelter and substrate‑shelter orientation on survival and growth of the megalopa and first crab instar Scylla tranquebarica - Thien, Fui Yin; Noorsyarinah Sanudin; Katsuyuki Hamasaki; Rossita Shapawi; Audrey Daning Tuzan; Zarinah Waheed; Yong, Annita Seok Kian (Springer Nature, 2025)
The present study aimed to investigate the effect of the substrate-shelter and substrate-shelter orientation on the survival and growth of the megalopa and first crab instar of Scylla tranquebarica. The substrate-shelter and substrate-shelter orientation experiments were conducted with or without sand substrate, in combination with a net and polyvinyl chloride pipe (PVC) as shelters, in triplicate groups for 14 days. In the orientation experiment, shelters were positioned either horizontally or vertically in the culture tank. Megalopae had metamorphosed into first and second crab instars on day 14. Both experiments exhibited a similar trend in observations: the second crab instar composition percentage (CP), total survival rate (SR), and total yield (TY) were significantly higher in the substrate group than the non-substrate group (P < 0.05); and the net shelter outperformed the PVC shelter, as indicated by the higher CP, SR, and TY. In the same shelter group, the horizontal shelter was more efficient than the vertical one, as shown by greater CP, SR, and TY. A substrate in combination with a horizontal net shelter is thus recommended for rearing purple mud crab megalopa and crab instar. This feasible rearing technique pro-motes consistent crab seed production in the hatchery to support sustainable mud crab aquaculture.